Behaviour and design of cold-formed lean duplex stainless steel lipped channel columns. (July 2016) - Anbarasu, M.; Ashraf, M.
Abstract: This paper presents a numerical investigation on the behaviour and design of lean duplex stainless steel (LDSS) lipped channel columns subjected to axial compression. Numerical models were developed using general purpose finite element (FE) package ABAQUS, and have been verified using experimental data available in the literature. Developed FE models included material nonlinearities as well as initial geometric imperfections. A comprehensive parametric study has been carried out covering a wide range of slenderness with different cross section geometries for the considered lipped channel columns. Column resistances obtained from the numerical study were used to assess the performance of the current Direct Strength Method (DSM) guidelines when applied for cold-formed LDSS columns; obtained comparisons showed considerable conservatism. A modified design method for LDSS lipped channels is proposed herein following DSM techniques, which provides considerably more accurate predictions for the considered cold-formed columns. Reliability of the proposed design equations is also presented showing a good agreement with both experimentally and numerically obtained results. Highlights: The finite element models were developed and calibrated against the test results reported. An extensive parametric study was performed comprising 64 fixed ended cold-formed lean duplex stainless steel lipped channel columns. Assessment of existing Direct Strength Method (DSM) and the modified DSM design methods using the obtained numerical results. New design rule were developed to predict the compression resistance for LDSS lipped channel columns. Reliability assessments of the existing and proposed DSM design approaches are presented.